TNM staging of neoplasms of the endocrine pancreas: results from a large international cohort study - Rindi, Guido; Büchler, Markus W.; Fischer, Lars (Journal of the National Cancer Institute, 2012)
AbstractBackground. Both the European Neuroendocrine Tumor Society (ENETS) and the International Union for Cancer Control/American Joint Cancer Committee/World
Published: 23 April 2012
Gesehen am 26.06.2018